Enhancing Residents' Warmth in Greeting Caregivers: An Inpatient Intervention to Improve Family-Centered Communication. Issue 3 (May 2021) - Bayer, Nathaniel D.; Taylor, April; Atabek, Zoey; Santolaya, Jacobo L.; Bamat, Tara W.; Washington, Nicole
Abstract : ABSTRACT: Hospitals are increasingly motivated to improve the patient and family experience and increase patient satisfaction scores. The manner by which a provider greets patients and their families sets the tone for the hospital stay. This study aimed to improve residents' greetings of caregivers in the inpatient pediatric setting to improve family-centered communication. The study was conducted from October 2017 to April 2018 at a single, urban children's hospital on a unit with patients primarily <5 years old. The intervention consisted of posting a prominent board outside of patients' rooms that (1) listed caregivers' preferred names (e.g., Mom/Dad, first names), (2) instructed residents to greet caregivers warmly by their preferred names, and (3) identified residents for families by name and photograph. During implementation, we conducted 5 Plan-Do-Study-Act cycles and surveyed 114 caregivers. Improvement was assessed using run charts. The primary outcome was the percentage of caregivers who rated residents' warmth of greetings as "excellent." This measure increased from a baseline median of 62.5%–84.4% with ≥6 consecutive postintervention points above the baseline median. The intervention improved caregiver-perceived quality of residents' greetings and could serve as a model for other hospitals to enhance provider-family rapport and improve communication. Abstract : Supplemental Digital Content is Available in the Text.